Analisis Dampak Regional Relaksasi Kebijakan Makroprudensial Loan to Value (LTV) Bank Indonesia terhadap Pertumbuhan Kredit Properti Periode Tahun 2016 s/d 2022 - Afrianty, Wienda; Soesilo, Nining I. (UI Scholars Hub, 2024)
Macroprudential policy is a countercyclical policy that aims to reduce over-optimism during economic booms by curbing excessive expansion and mitigating over-pessimism during busts to ease credit contractions. Therefore, a macroprudential policy such as Loan to Value (LTV) aims to mitigate risks in the property sector. Bank Indonesia has relaxed LTV policy from June 2015 to December 2023. Research findings using individual bank quarterly data indicate that the relaxation of the LTV policy positively impacts property credit growth with a lag time of two quarters after the policy implementation. However, when analyzing on a regional basis, only positively and significantly impacts credit property growth in Java.